Asymbiotic Seed Germination of Thunia alba, a Variable Orchid in an Isolated Karst Hill of Xishuangbanna, Yunnan, China (Plant Tissue Culture and Biotechnology, 2020)
Asymbiotic seed germination of Thunia alba (Lindley) H.G. Reichenbach was tested on different media in order to propagate and preserve its genetic diversity. In addition different plant hormones were used in the similar germination experiments. Results from these experiments revealed that Knudson medium (KC) had the best germination ability but Mitra and modified Murashige and Skoog (MS) also showed good responses for growth and root formation in the seedling after eight weeks. Coconut water (CW) was the most efficient for promoting germination and growth, addition of 0.046 μM and 0.46 μM Kn also induced better germination rate and formation of leaves. The seedlings after eight months were transferred and acclimatized to grow in the garden on a medium containing bark and crushed concrete blocks. Although the species is amongst the rare orchid species that can successfully propagate asexually in the wild it is demanding for substrate and climatic conditions.Plant Tissue Cult. & Biotech. 30(2): 189-197, 2020 (December)